Newton type iterative methods with higher order of convergence - Jain, Pankaj; Bhatta, Chet Raj; Jnawali, Jivandhar (J. Numer. Anal. Approx. Theory, 2016)
Newton type iterative methods are obtained with higher order of convergence and with higher efficiency. The methods have been compared with the similar existing methods of recent times.